Attribution tendency and its relationship with actual and perceived proficiency. - Setsuko Mori,; Thang, Siew Ming; Nor Fariza Mohd Nor,; Vijaya Latshmi Suppiah,; Oon, Sok Imm (Penerbit UKM, 2011)
Attribution theory suggests that people attribute different causes for those areas in their lives where they perceive themselves as having succeeded or failed. These perceived causes may be classified into three causal dimensions: locus of control, stability, and controllability. Using attribution theory, this study examines Malaysian university students’ attributions for success and failure in learning English as a second language. The study attempts to investigate their perceived reasons for successes and failures on actual language learning tasks, and explores whether their attribution tendencies vary depending on their actual and perceived proficiency. Based on attribution theory, two versions of a questionnaire (one for success and one for failure) were administered to 2152 students at six different universities in Malaysia. Students were required to pick an activity at which they had scored particularly poorly in the previous semester. In the second part of the questionnaire, the students were asked to rate the twelve causes for success or failure on a six point Likert scale. The findings showed that high proficiency learners and those who perceived themselves as high proficiency learners attributed success to their own effort and ability more than mid and low proficiency learners. On the other hand, when it comes to failure experiences, high proficiency learners and those who regarded themselves as having high proficiency showed a stronger tendency to ascribe their unsuccessful